2015
DOI: 10.1039/c4ra10381e
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into flavones as protein kinase CK2 inhibitors derived from a combined computational study

Abstract: Binding conformation of flavone inhibitors to protein kinase CK2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…17 In recent years, many studies had indicated that computational approaches can timely provide very useful information and insights for drug development. [18][19][20] Such as predicting functions of proteins, 21 structural bioinformatics, 22 molecular docking, and predicting drug-target interaction [23][24][25] were widely welcome by science community. Quantitative structure-activity relationship (QSAR) method, as a powerful quantitative methodology, were proved to be one of the most promising and successful methods for rapidly predicting the biological activity and/or toxicity of chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…17 In recent years, many studies had indicated that computational approaches can timely provide very useful information and insights for drug development. [18][19][20] Such as predicting functions of proteins, 21 structural bioinformatics, 22 molecular docking, and predicting drug-target interaction [23][24][25] were widely welcome by science community. Quantitative structure-activity relationship (QSAR) method, as a powerful quantitative methodology, were proved to be one of the most promising and successful methods for rapidly predicting the biological activity and/or toxicity of chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Using molecular docking, key amino acids (Asp335, Tyr383, and Gln384) were identified owing to the docking of flexible ligand into rigid receptor. MD analysis can support these docking results through the fluidity of their complexes, or identify new key interactions [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking is an increasingly significant method in realizing the foundation of ligand-protein recognition. 17 To evaluate the potential interaction of the vitamins and XO at the atomic level, AutoDock 4.2 (Scripps, USA) under a simulation environment (298.15 K) was applied. XO is a homodimer, each monomer acts independently with a molybdenum (Mo) center, two [2Fe-2S] clusters and an FAD cofactor.…”
Section: In Silico Molecular Docking Studymentioning
confidence: 99%